Proses Mendapatkan Label Halal untuk UMKM Bu Endang - Johan, Mhd.; Syaifullah; Winda Evyanto; Gaguk Rudianto; Zia Hisni Mubarak; Yunisa Oktavia; Simanjuntak, Dairi Sapta Rindu (ASOSIASI IDEBAHASA KEPRI, 2025)
The purpose of this service is to help small traders increase their sales turnover. Before getting halal certification, micro businesses must go through several processes. The first process they do is create a NIB. The process of creating this NIB is created by a business assistant. Here, business actors prepare their KTP, NPWP, must have a cellphone number, and must have an email. In creating a NIB, business actors provide data such as how long they have been doing business, goods for sale, business location, and business capital. After the NIB is complete, then start registering for sihalal, the sihalal registration process also requires filling in data and preparing an KTP. To fill in this data, business actors are assisted by a business assistant, but if the business actor does not understand, the business actor can submit it to the business assistant. This filling process will involve more data, then in inputting materials there are two types, the first is certified materials and non-certified materials. Then here we also fill in the cleaning agent and packaging. After the data is filled in, we need to verify the data that has been filled in. After that, we input the product and its photos. After we finish, we make a way to make the product. After that, send it. We wait for the assistant process, after the assistant approves, then we send it again, then the assistant approves again and sends it to P3H, after P3H is completed, it is sent to the fatwa commission after being approved by the fatwa commission, the certificate is issued.